Analysis of EFL reading comprehension skills among students of the second baccalaureate at centro de estudios La Moderna in the school year 2022-2023. - Mosquera Velásquez, Luis Iván (2023)
Humans weren't born to read; reading is a longitudinal process that must be taught and developed with time. Students learned to read in their native language L1 before acquiring another language. The research study aims to ease the acquisition and understanding of a new language L2, by implementing L1 effective reading comprehension methods, techniques, and strategies. A qualitative method with the use of a case study analysis was chosen since it allows the researcher to narrate what people do in their everyday lives without influencing the environment. The study was conducted in La Moderna high school located in Samborondon-Guayaquil in the scholastic year 2022-23. A total of 24 EFL second baccalaureate students and seven teachers participated in the study. The findings of the study not only determined the relationship and similarity of L1 Spanish reading skills with L2 English but also that these skills could be transposed to the target language. The research findings will benefit La Moderna staff including students and parents. Equally important, the research findings will support any educator interested in transposing L1 effective reading skills for long-term reading comprehension achievement into L2 environment. Finally, as more people continue to show interest in learning a second language, it is essential to find common grounds to explore existing reading skills from L1 to be transposed and used in second language acquisition.